2014
DOI: 10.1007/s10980-014-0039-6
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and interspecific interactions and environmental factors determine spatial–temporal species assemblages of rodents in arid grasslands

Abstract: Many factors have been shown to affect species assemblages of a community, but studies using long-term spatial-temporal community data are still lacking. In this study, by using population abundance data of 14 rodent species over 25 years in 21 sampling sites, we investigated the effects of taxonomic relation, density dependency, species interaction and climate variation in determining spatial-temporal species assemblages of rodents in arid grasslands of Inner Mongolia in China. By the use of GAMM analysis, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…As a result, we also found some evidence of resource partitioning, with P. daltoni occupying a higher trophic level where species richness was highest at the northern site. These results are consistent with the findings of Jiang et al (2015) , who demonstrated the importance of intraspecific interactions and environmental variables in explaining spatial-temporal communities in small mammals from arid grasslands in China. Additionally, Codron et al (2015) reported species occupying similar isotopic niches exhibited spatial separation for small mammals in South Africa.…”
Section: Discussionsupporting
confidence: 92%
“…As a result, we also found some evidence of resource partitioning, with P. daltoni occupying a higher trophic level where species richness was highest at the northern site. These results are consistent with the findings of Jiang et al (2015) , who demonstrated the importance of intraspecific interactions and environmental variables in explaining spatial-temporal communities in small mammals from arid grasslands in China. Additionally, Codron et al (2015) reported species occupying similar isotopic niches exhibited spatial separation for small mammals in South Africa.…”
Section: Discussionsupporting
confidence: 92%
“…Interactions among individuals-both within and between species-are diverse, complex, and contingent on local and regional issues, ranging from species composition to habitat and climatic influences. In general, intraspecific competition is generally stronger than interspecific interactions (Tong et al 2012;Jiang et al 2015), but the relative roles of competition and predation are less clear. The former may be the stronger influence on habitat selection for collared and brown lemmings (e.g., Dupuch et al 2014) and more strongly depress population size for red-backed voles (Lemaître et al 2010), whereas the latter appears to be a more proximal factor in habitat selection of gerbils (Abramsky et al 1998).…”
Section: Conclusion and Prospectusmentioning
confidence: 99%
“…Competition has been a dominant theme throughout the history of ecology, and is an essential mechanism underlying much of natural selection. Intraspecific competition takes many forms and may be more common and significant than interspecific competition (Jiang et al 2015). Intraspecific competition implies density-dependence (DD) and this is essential to logistic growth and considerations of carrying capacities and resource limitation.…”
Section: Intraspecific Competitionmentioning
confidence: 99%
“…The level of aggression displayed by competitors during such interactions is influenced by the potential benefits obtained by winning a contest, and the risks faced during confrontations (Maynard-Smith 1982, Enquist and Leimar 1987, Innocent et al 2011. Accordingly, fluctuations in resource availability, competitive ability, or changes in the population density of competitors are likely to influence the coexistence of antagonistic competitors (Brown 1989, Sih et al 2012, Flynn and Pereira 2013, Jiang et al 2015.…”
Section: Impacts Of Worker Density In Colony-level Aggression Expansmentioning
confidence: 99%